Energy Security and Economic Resilience of RA in the Context of Current Geopolitical Developments - Karapetyan, Liana (Bulletin of Yerevan University G: Economics, 2025)
This article analyzes the current manifestations of Armenia’s energy security and economic resilience in the context of recent geopolitical changes. It assesses the current state of Armenia’s energy security and economic resilience based on key indicators used in international policy and well-supported in the academic literature. The analysis shows that the adopted indicators - such as energy intensity, external energy dependence, and measures of supplier concentration - have methodological limitations and do not fully reflect the country’s structural and geopolitical specificities. The main goal of this study is to examine the limitations and gaps of commonly used energy security indicators in the context of Armenia’s green transition policies and current geopolitical developments. By analyzing various indicators of energy security and economic resilience and contextualizing them for the Armenian economy, a multi-component qualitative assessment has been investigated, showing that these indicators alone do not provide a comprehensive picture and do not fully reflect the country’s structural and geopolitical characteristics. Energy policy can be more effective and targeted when informed by clear and integrated assessments of these factors. Such an approach is essential to support Armenia’s long-term energy security and economic resilience.
Keywords: energy security; Economic resilience; Geopolitical risks; Energy intensity; Primary energy supply